INVESTIGATION INTO RADIOLOGICAL ENVIRONMENT IN A SO CALLED “CANCER VILLAGE”: THACH SON COMMUNE, PHU THO PROVINCE (VIETNAM) - NGUYEN , QUANG LONG; TRAN , TUYET MAI; TRAN , THANH MINH; DUONG , VAN THANG; DOAN , THUY HAU; DINH , NGON (Nuclear Science and Technology, 2012)
A survey for radiological environment was conducted in the 2010 in the Thach Son commune, Lam Thao district, Phu Tho province (Viet Nam) known as a “cancer village”. There the rate of cancer cases is unusual high among the population and the environmental deterioration was suspected to be the reason for the disease. Radioactive contaminant from the apatite mineral used for the phosphorus fertilizer industry in the region was thought to be one of the main “culprits” causing the cancer and needed to be evaluated. The survey includes measuring the gamma dose rate in the field and collecting samples for the TENORM analysis in the laboratory. The gamma dose rate in the air at 1 m above the ground was recorded in 244 points using TCS 171 (Aloka) survey meter. 33 soil samples, 23 samples of vegetable and grain as well as apatite mineral were collected for the gamma spectrometric analysis using HPGeD. 21 samples of water from dug wells were taken for total alpha and beta radioactivity measurement in the laboratory. Outdoor and indoor 222Rn concentrations in the surface air in 35 points was monitored using active and passive methods with respective equipment. Results obtained showed that the average gamma dose rate in outdoor air at 1 m above the ground is (0.086 ± 0.018) µSv/h, and the average indoor dose rate is (0.109 ± 0.021) µSv/h resulting in an annual effective dose in the investigated area is of nearly 0.9 mSv a year. The radioactivity concentrations of uranium-238, thorium-232, and K-40 in soil are 35.7 ± 5.1, 52.8 ± 5.8 and 747.4 ± 119.3 Bq/kg, respectively. Given that the background of the cosmic rays, at a elevation of less than 100 m asl, is 32 nGy/h, then the gamma dose rate in the surface air calculated based on the Beck [2000], could be as high as 0.088 ± 0.012 µSv/h. The average total alpha and beta activity in water samples is ranging from 12.8 to 30 and 138 to 300 mBq/L, respectively. The outdoor 222Rn concentrations in the surface air was around 10 Bq/m3. The radioactivity range of K-40, progeny of the radium-226 and actinium- in food was found to be as high as 44.7-921.0,und to be as high as 44.7-921.0; LOD-21.2, and LOD-31.3 Bq/kg, respectively. The radioactivity concentrations found in all the samples collected are falling in the range of ordinary environment in Viet Nam. The finding shows obviously that the radioactivity from the chemical industry in the study region has low impact to the human health in the region meaning that there is no reason to suspect that the radioactive environment could be a cause for the cancer disease among the population of the Thach Son commune.